Abordaje del paciente y sus familiares: algo más que la relación médico-paciente - Vílchez-Rivera, Stalin (2019)
To approach a patient is as important as dealing with family members and not only we should see it as a formal process but the physician must be presentable, educated, human, ethical, personable, educator, communicative, neutral, decent, biosecure, safe and educated, which will allow to obtain better clinical data to reach the diagnosis with greater approximation, to avoid the breakdown in the patient-doctor relationship and to diminish the legal processes.